'Top heavy' systems and quality of health care: A survey of select departments in R.G. Kar Medical College and Hospital, India - Zakir Husain; Saswata Ghosh; Bijoya Roy (Social Medicine Publication Group, 2009)
The paper is based on a primary survey of 1095 patients from the Medicine, General Surgery and Cardiac departments in R.G. Kar Medical College and Hospital (a major public sector health care institution in the metropolitan city of Kolkata, India). The results show that public health care institutions remain a vital life support system of the poorer sections of the population. However, this is not a matter of choice, but necessity. The breakdown of the three tiered referral system in the region has resulted in the Hospital, originally conceived as a super specialty hospital and referral health care institution for patients from the adjacent district of North 24 Parganas, functioning as a diagnosis unit. The resultant pressure has exceeded the carrying capacity of the institution and led to poor quality of health care in the Hospital. Revitalizing lower level institutions is therefore essential not only to increase accessibility of health services, but also to ensure efficiency in higher level health care institutions.